2021
DOI: 10.1158/2159-8290.cd-20-0833
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment–Derived R-spondins Enhance Antitumor Immunity to Suppress Tumor Growth and Sensitize for Immune Checkpoint Blockade Therapy

Abstract: Natural killer (NK) cells and T cells are key effectors of antitumor immune responses and major targets of checkpoint inhibitors. In multiple cancer types, we find that the expression of Wnt signaling potentiator R-spondin genes (e.g., RSPO3) is associated with favorable prognosis and positively correlates with gene signatures of both NK cells and T cells. Although endothelial cells and cancer-associated fibroblasts comprise the R-spondin 3–producing cells, NK cells and T cells correspondingly express the R-sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…found that the expression of the Wnt signaling booster gene RSPO3 was linked to a better prognosis. Exogenous expression of RSPO3 in tumors can increase the cytotoxic effector cells infiltration and function, resulting in tumor regression [ 9 ].…”
Section: Molecular Mechanism Of Rspos Involved In Tumor Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that the expression of the Wnt signaling booster gene RSPO3 was linked to a better prognosis. Exogenous expression of RSPO3 in tumors can increase the cytotoxic effector cells infiltration and function, resulting in tumor regression [ 9 ].…”
Section: Molecular Mechanism Of Rspos Involved In Tumor Progressionmentioning
confidence: 99%
“…Bioinformatic analyses such as gene enrichment found that RSPOs are widely involved in immune regulation. For example, the latest study reported that RSPO increased tumor sensitivity to anti-PD-1 therapy, highlighting an unprecedented treatment approach [ 9 , 10 ]. Immune checkpoint blockade has been widely used in the clinical treatment of tumors, but the lack of tumor antigens and the failure to effectively initiate adaptive immunity led to poor efficacy of immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…As a crucial immune cells, natural killer (NK) cells are an important immune factor in the body's antitumor and anti‐infection processes. Increased infiltration of NK cells and cytotoxic cells leads to enhanced immune system function, increased efficacy of anti‐PD‐1/PD‐L1 therapy and improved prognosis 68 . Due to the reduced expression of MHC I molecules on the surface of CSCs and the dysregulation of excitation and inhibition signals on the surface of NK cells, CSCs can be specifically targeted to enable NK cells to exert killing effects 69 .…”
Section: Collusion Between Cancer Stem Cells and Immune Cellsmentioning
confidence: 99%
“…The expression of the Wnt signaling protein BCL9L in soft tumors correlates positively with worsening clinicopathological features in advanced stages, which may be related to Wnt signaling promotion of epithelial cell proliferation and EMT 78 . However, it has been found that increased expression of R‐spondin 3 in the Wnt pathway in NK cells and CD8 + T cells could exert antitumor effects by activating the immune system with enhanced efficacy of ICB 68 . Therefore, the role of Wnt signaling expression and its sites in tumor therapy remain to be further clarified (Figure 2).…”
Section: Signaling Pathways and Targeting Strategies For Cancer Stem ...mentioning
confidence: 99%
See 1 more Smart Citation